Application of spatial classification rules for remotely sensed images - Stabingis, Giedrius; Stabingienė, Lijana (Lietuvos matematikos rinkinys, 2014)
In this paper the remote sensed image classification example using spacial classification rule with distance (SCRD) is examined. This supervised classification method was first presented in paper [11]. This method is improved version of earlier method PBDF [4, 10, 9], during the classification it incorporates more spatial information. The advantage of this method is its ability to classify data which is corrupted by Gaussian random field and it is typical to remotely sensed images classified in this letter which are corrupted by clouds. Classification accuracy is compared with earlier method and with other commonly used supervised classification methods.
Keywords: image classification; spatial classification rules; supervised classification